Annual and seasonal home range characteristics of female Asiatic black bears in Karuizawa, Nagano Prefecture, Japan - Yamamoto, Toshiaki; Tamatani, Hiroo; Tanaka, Junpei; Yokoyama, Shotaro; Kamiike, Kumiko; Koyama, Masaru; Seki, Kanako; Kakefuda, Sayoko; Kato, Yuko; Izawa, Natsumi (Ursus (International Association for Bear Research and Management), 2012)
We characterized annual and seasonal home ranges (HR) of 27 female Asiatic black bears (Ursus thibetanus) during 2003–11 in Karuizawa, Nagano Prefecture, Japan. Mean annual HR size for bears calculated by the 95% fixed kernel method was 10.0 km2 (SD  =  8.5) and differed depending on the year. However, annual HR sizes were not affected by reproductive status (with or without cubs) or age (subadult or adult). Home ranges tended to be larger in summer than in autumn. We speculate that a contributing factor to differences in HR size was annual or seasonal fluctuation of food resources. Annual shifts in HR centers and HR overlaps were estimated to be 1.2 km (SD  =  0.9) and 0.55 km (SD  =  0.13), respectively. Seasonal shifts in HR centers and seasonal overlaps were 1.1 km (SD  =  1.1) and 0.54 km (SD  =  0.12), respectively. Together, these results suggest that female Asiatic black bears in our study area do not migrate long distances seasonally or annually.